PEMBERIAN KOLOSTRUM PADA BAYI BARU LAHIR: PERSPEKTIF PARITAS DAN DUKUNGAN KELUARGA - Rahakbauw, Grenny Zovianny; Sulistiyowati, Dwi; Sidabutar, Rasmina Anggi Permatasari; Arifin, Hasriany; Ayu, Yennyka Dwi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Psychosocial development of school-age children are adaptive child has a motivation to learn, started to doing homework and active and playing with their friends. School-age children in Kapujan have a problem where the psychosocial development of the survey in March 2016 of 10 school-age children (6-12 years), by conducting interviews. Obtained, 6 children have lost their parents in the next 1-4 years ago with 4 children haven’t with psychosocial development. Somestimes, deviate behavior is difficult to learn, decreased school achievement and be subdued children. While the 4 children who did not experience the loss of a parent. 3 of them psychosocial normal. The goal of researchers is to look at the relationship have lost their parents to the psychosocial development of children in Kenagarian kapujan 2016, this study uses the method description correlative approach crosscektional and instrument tool used a questionnaire with a student population of 33 persons were made in the sample using techniques pourposive sampling